Preparation and characterization of an efficient zeolitic material from a local natural kaolinitic clay and its uses in the elimination of an organic dye - Chinar, Tahani Achouak; Benbouzid, Mohammed (European Journal of Chemistry, 2016)
The zeolitic porous material was prepared from kaolinitic clay (DD1 from Gebel Debbagh, Algeria) using a cheap and easy process to insert a sodium ion into the kaolinitic clay structure. The obtained zeolitic Linde Type-A (LTA) material was characterized by elemental analysis, infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy and X-ray diffraction techniques. The adsorption capacity of the zeolitic porous material was tested with methylene blue. The best correlation of experimental results was obtained with the Langmuir model giving a Qmax of 11.5 mg/g indicating a favorable process for the adsorption of the dye.